Results of Medical Research Council trial UKALL IX in acute lymphoblastic leukaemia in adults: report from the Medical Research Council Working Party on Adult Leukaemia. - Durrant, I; Richards, S (1993)
The MRC UKALL IX trial for patients with untreated ALL aged 14 years and over was open to new patients from July 1980 to April 1985. 266 patients were randomized between two induction schedules. M (involving intermediate dose methotrexate with folinic acid rescue) and D (involving daunorubicin). Schedule M resembled that used in the previous MRC adult ALL trial (UKALL VI), while schedule D was somewhat more intensive. No difference in disease-free survival was found between the treatment arms, but patients on the daunorubicin arm went into remission earlier. The overall remission rate was 87%, which is at least as good as in contemporary studies elsewhere; factors predictive of a lower remission rate were older age and higher WBC. For those who entered remission. WBC, age and sex were the most important prognostic factors. Time to achieve remission was not a significant factor after allowance was made for these. An historical comparison does not show any improvement over the preceding MRC adult trial, although the subsequent trial does show a modest improvement at present. Because the improved outlook seen in children is not apparent in adults, and no other randomized trial has demonstrated substantial benefit for any particular regimen, the next trial, UKALL XII, will be investigating the benefit or otherwise of bone marrow transplantation.